Achievement of sustained deep remission with adalimumab in a patient with both refractory ulcerative colitis and seronegative erosive rheumatoid arthritis - G. Andrisani (Reumatismo, 2013)
Inflammatory bowel disease (IBD) is commonly associated with peripheral inflammatory arthritis, and it has been estimated that as many as 12% of IBD patients report these manifestations. However, rheumatoid arthritis (RA) is rarely associated with ulcerative colitis (UC). Among all the biological agents available, nine have been currently approved for the treatment of RA. Conversely, only Infliximab and recently Adalimumab have been approved for UC. In particular, the efficacy of Adalimumab in UC has been demonstrated by both recent randomized controlled trials and real-life studies. Moreover, Adalimumab is a well-established treatment for RA. Herein, we describe a patient with RA and UC treated successfully with ADA.